2007
DOI: 10.1007/s00468-007-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Variant maturity in seed structures of Pinus albicaulis (Engelm.) and Pinus sibirica (Du Tour): key to a soil seed bank, unusual among conifers?

Abstract: The seeds of Cembrae pines are dispersed by nutcrackers (Genus Nucifraga), which cache seeds in soil during autumn. The dispersal and establishment of seedlings via this mutualistic relationship is highly successful. On the other hand, irregular quality of seed crops and lack of detailed knowledge on germination process of Cembrae pine seeds hamper effective seedling production in the nursery. Therefore we studied basic structures and maturity of whitebark pine (Pinus albicaulis Engelm.) and Siberian stone pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…(median seed mass: 214 mg), which elucidated that seed morphological traits might not be an adaptive indicator in predicting the light requirement of seed germination. It was also reported that the mechanical restraint of the thick seed coat was diminished as the P. sibirica embryo became truly mature by undergoing natural cold stratification from winter to early spring (Tillman-Sutela et al, 2008), which was also true for P. koraiensis. The light requirement for the germination of P. koraiensis might be created after seed prechilling, as has been reported for P. strobus (Toole et al, 1962).…”
Section: Similar Germination Percentages Under Leafless Canopy and Inmentioning
confidence: 94%
“…(median seed mass: 214 mg), which elucidated that seed morphological traits might not be an adaptive indicator in predicting the light requirement of seed germination. It was also reported that the mechanical restraint of the thick seed coat was diminished as the P. sibirica embryo became truly mature by undergoing natural cold stratification from winter to early spring (Tillman-Sutela et al, 2008), which was also true for P. koraiensis. The light requirement for the germination of P. koraiensis might be created after seed prechilling, as has been reported for P. strobus (Toole et al, 1962).…”
Section: Similar Germination Percentages Under Leafless Canopy and Inmentioning
confidence: 94%
“…However, the suspensor remnants have a further role during germination: when moistened, they swell and facilitate protrusion of primary root through the micropyle. 6,16 There are no reports concerning gymnosperm seeds, but it has been suggested that in angiosperms the continued growth of the suspensor may be inhibited by the embryo proper during early stages of development. 4 When suspensors die, subordinate embryos loose their fixed position within the Scots pine seed as well as their source of nutrition, which may lead to starvation if subordinate embryos are not capable of utilizing nutrients from the CC fluid.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 The cell wall, plasma membrane and nuclear envelope of the starch-rich cells break down with the release of cell debris and nucleic acids into the CC (Vuosku et al unpublished), where the remnants form a malleable zone between the ESR and the developing embryo 6 (Fig. 1E).…”
Section: The Many Faces Of Cell Death In Scots Pine Embryogenesismentioning
confidence: 99%
See 2 more Smart Citations